1998
DOI: 10.1590/s0034-71081998000400018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the thyroid gland during the reproductive cycle of the male vespertilionid bat, Scotophilus heathi

Abstract: The aim of present study was to compare the changes in thyroid gland with the reproductive cycle of S. heathi. Thyroid showed marked seasonal variation in weight, quantity of colloid and follicular epithelial height, suggesting the thyroid gland to be inactive during quiescence and winter dormancy and active during the time of recrudescence and breeding similarly to the testicular cycle. Plasma thyroxin (T 4 ) concentration showed a significant seasonal change with high concentration during breeding and post-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…It has been our experience that chiropteran peptide hormone shows greatest cross-reactivity with antibodies generated against human. This has been reported and validated from our laboratory for T 3 and T 4 measurements in another species, S. heathi [20]. The T 3 and T 4 assays were performed by adding 100 µl serum samples for T 4 , and 50 µl serum samples for T 3 to 100 µl of labelled thyroid hormone (approximately 10,000 counts per minute), mixing them and then adding 100 µl of the respective antiserum.…”
Section: T 3 and T 4 Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been our experience that chiropteran peptide hormone shows greatest cross-reactivity with antibodies generated against human. This has been reported and validated from our laboratory for T 3 and T 4 measurements in another species, S. heathi [20]. The T 3 and T 4 assays were performed by adding 100 µl serum samples for T 4 , and 50 µl serum samples for T 3 to 100 µl of labelled thyroid hormone (approximately 10,000 counts per minute), mixing them and then adding 100 µl of the respective antiserum.…”
Section: T 3 and T 4 Assaysmentioning
confidence: 99%
“…It has been also suggested that the level of plasma gonadotrophin was associated with hypothyroidism [6,12]. Instead of many unique features, studies related to thyroid function in bats are limited and the few available studies, are restricted to the temperate region bats [7,14,15,20,34,35]. T. longimanus is a subtropical emballonurid bat; it shows differential rate of fetal growth in its two successive pregnancies [19].…”
Section: Introductionmentioning
confidence: 99%
“…Today we know that some bats of the Vespertilionidae and Rhinolophidae families show a temporal asynchrony in the development and functioning of the male reproductive organs [60]. Specifically, the development of the testes and the process of spermatogenesis take place mainly in the summer months, while the maximum development of the epididymis and accessory sex glands, the expression of libido, and mating, do not occur until the autumn [56,[61][62][63][64]. This asynchrony results in an unusually long period of sperm storage in the epididymis, which may extend for several months after the testes have completely regressed [55].…”
Section: Prolonged Sperm Storage In the Epididymismentioning
confidence: 99%
“…Another proposal to consider relates long-term sperm storage to the epididymal maturation process. In the case of the vespertilionid Mexican big-eared bat, in addition to being a species that manifests asynchrony in the development of the male's sexual functions [56,[61][62][63][64], it also maintains the sperm in the epididymis for up to 5 months after the testes have fully regressed [60].…”
Section: Maturation and Prolonged Storage In Mexican Big-eared Bats (mentioning
confidence: 99%
“…Thyroid gland showed seasonal variation in weight, quantity of colloid and follicular epithelial height, suggesting to be inactive during quiescence and Winter dromency and active during time of recrudescence and breeding time similarly (8). When the gland is inactive, the colloid is abundant, the follicles are large and the cells which lining them are flat.…”
Section: Introductionmentioning
confidence: 99%